A study on factors affecting housing preference of first time home buyers among university students in Klang Valley area - Lee, Michelle Mong Xin (2024)
This research explores the housing preferences of university students buying their first home in the Klang Valley area. In this bustling urban setting, they encounter distinctive challenges while balancing their academic pursuits with homeownership.